The effect of the quality of external audit on the quality of application of international standards )An applied research in a sample of private joint stock banks listed on the Iraq Stock Exchange( - Qasim Chaloop Menshid; Fayhaa Abdullah Yaqoob (Journal of Madenat Alelem University College, 2021)
The research aims to measure the impact of the quality of external audit on the quality of application of international standards, for a sample of private joint-stock companies listed on the Iraq Stock Exchange, where the research sample included (10) private and listed joint-stock banks in issuing their financial statements for the period from (2010-2018) as well For companies and auditing offices charged with auditing these banks, the research relied on two main models of measurement, whereby the first model reflects the assumed relationship between independent variables represented in the characteristics of external audit quality and measuring the extent of their impact on the dependent variable represented in the quality of application of international standards. Second, the Tobin`s Q scale has been adopted to measure the quality of application of standards (IFRS) according to the formula (Chung & Pruitt, 1994), and the SPSS statistical program has been relied on to analyze the data and reach the results, and the research has found the quality of the audit companies and audit offices that have audited the research sample banks and the lack of quality in applying the standards,The absence of a significant correlation between the quality of the external audit and the specific factors specific to the specifications of the audit firm or office and the factors related to the customer specifications on the quality of the application of the standards to banks in the research sample.